Based on a Large Solar Device Technological Features of Selection of Local Raw Materials (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article highlights the features of selecting local raw materials for obtaining heat-resistant ceramic tiles made on the basis of a large solar furnace. A technical description of the substances contained in the amesite mineral of the serpentine in the Kumushkon mountains of the Tashkent region is presented.